DZIENNIKARSTWO OBYWATELSKIE - PRÓBA SOCJOLOGICZNEGO OPISU - Drozdowski, Rafał (Wydział Prawa i Administracji UAM, 2008)
The paper touches upon a new, at least in Poland, phenomenon known as citizen journalism. It is also treated as a pretext to carry out more general deliberations on the completely new challenges and dilemmas facing the contemporary citizen society. Citizen journalism is developing dynamically and seems to confirm the thesis about the vitality of citizen society. At the same time, however, the phenomenon o f citizen journalism prompts one to pose a number of new questions including such as: isn’t today’s citizen society being deliberately pushed to the Internet with the result that although its initiatives are conveyed globally, they also become merely niche ones; or is the Web 2.0 formula (on which most o f the examples o f citizen journalism are based) a chance to increase citizens autonomy;, or is it rather a vehicle of social self-supervision, and to what extent is citizen journalism an alternative to the existing, established media order.
CITIZEN JOURNALISM: AN ATTEMPT OF A SOCIOLOGICAL DESCRIPTION